Sur certaines mystifications épistolaires, ou «le dit et le non-dit» dans la lettre et le roman par lettres - Rabsztyn, Andrzej (Romanica Silesiana)
Andrzej Rabsztyn, on the basis of Balzac's letters to Ewelina Hanska, shows a game between the truth and falsehood, the said and unsaid in the real and fictitious letters in the period of the peak development of the art of letter-writing and epistolary novel. Keywords: correspondence; epistolary novel; intentional silence; Balzac; Mrs Hańska